Συμμετοχική πλατφόρμα συγκέντρωσης και διάδοσης της πληροφορίας στις αστικές συγκοινωνίες - Μάρκου, Ελένη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών, 2016)
The scope of this thesis is the development of a fully functional, social network based application, built on the idea of crowdsourcing allowing public transport passengers to share organized and structured information on public transportation. Such shared information could lead to a better informed decision making by the users about their own journeys, and enable ppublic transport operators to gather information about their service quality and therefore , improve it. After the application development, usability tests were conducted among a group of potential users, which led to useful feedback about the work carried-out and the potential range of an application with these characteristics. This work can be seen as a strating point to the integrations of the addressed concepts in larger scale projects related to mobility.